Improving The Egg Quality Trough Addition Of Green Tea In Diet On Laying Hen (Faculty of Animal Science Universitas Brawijaya, 2010)
The Research was conducted to study the effect of green tea addition in diet to egg weight, egg number, egg yolk colour , fat level and cholesterol level of egg yolk on laying hens. The materials used were 72 laying hens of 28 weeks old. The method of the research was experiment arranged in Completely Randomized Design. The treatment were green tea addition levels were 0 %, 1 %, 2 %, and 3 %. The variables observed were egg weight, egg number, egg yolk colour, fat level and cholesterol level of egg yolk. The result showed that green tea had no significant effect (P> 0.05) on egg weight, egg number and egg yolk colour, but significant effect (P<0.05) on fat level and cholesterol level of egg yolk. The conclusion was green tea addition 3 % in diets, had not decreased on egg weight, egg number and not effect on egg yolk colour, but had decreased fat level and cholesterol level of egg yolk on laying hens. The suggested were on management of laying hen, so addition 2 % green tea on diets for reducing fat level and cholesterol level of egg yolk, with optimal egg production. Keywords : Laying hen, Green tea, Egg yolk colour, Fat, Cholesterol